Striving for our own spot while avoiding the embrace of the other. An architectural problem of today - Rodrigues, Ana Luísa (2021)
The COVID-19 outbreak in 2020 somehow changed our lives, at least for a while. The public spaces were no longer able to be shared by anyone, as an extension of our daily use space. Our existence’ space did shrink abruptly. The home was also the office, the school, the restaurant, the cinema, the gym, and the playground at the same time. Any house turns out to be the most crowed and almost unbearable place of the world. Now we’re striving for our own spot, while avoiding the embrace of the other, everywhere. Even at home. The question of our own privacy and safety gains new meaning today. Particularly in urban and dense areas, it became an architectural problem that urges to be unraveled. It’s time to rethink the domestic space and the nearby space – as the new need of an outside domestic space – while we crave to maintain our health and sanity. Thus, the aim of this paper insists mainly on how to keep any space opened and free, but simultaneously private and controlled, regarding the domestic realm. Through two filters of approach: the dwelling and the street level of the city, it aims to reflect upon the broad issues of individual isolation and privacy in order to outline some solutions to ease the problem somehow.